1997
DOI: 10.1016/s1090-3801(97)90067-7
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐receptor control of the amplitude and duration of the neuronal responses to formalin in the rat spinal cord

Abstract: The GABAergic inhibitory system in the dorsal horn of the spinal cord has been implicated in the modulation of pain, including the control of nociceptive transmission during inflammation. This electrophysiological study examined the effects of the GABAA and GABAB receptor antagonists, bicuculline and CGP35348, on the magnitude and duration of the formalin response. The responses of spinal nociceptive dorsal horn neurones to subcutaneous injection of formalin into the hindpaw in the anaesthetized rat were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…At physiologic pH GABA is poorly permeable to the BBB but the pH of the CSF is acidic relative to the plasma, which makes GABA esters prodrugs that cross the BBB release GABA in the CNS through the action of esterases . GABA B receptors are involved in the modulation of nociception at the spinal cord and brainstem . Recently, it was demonstrated that the activation of GABA B receptors in the thalamus by baclofen, an agonist of GABA B receptor, or blockage by the antagonist CGP35348, induced an antinociceptive effect .…”
Section: Discussionmentioning
confidence: 99%
“…At physiologic pH GABA is poorly permeable to the BBB but the pH of the CSF is acidic relative to the plasma, which makes GABA esters prodrugs that cross the BBB release GABA in the CNS through the action of esterases . GABA B receptors are involved in the modulation of nociception at the spinal cord and brainstem . Recently, it was demonstrated that the activation of GABA B receptors in the thalamus by baclofen, an agonist of GABA B receptor, or blockage by the antagonist CGP35348, induced an antinociceptive effect .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, spontaneous nociceptive behavior is facilitated by GABA A receptor antagonists (Kaneko and Hammond, 1997) and inhibited by GABA A receptor agonists (Dirig and Yaksh, 1995; Kaneko and Hammond, 1997) in the formalin model. This behavioral profile is mirrored by changes in activity in dorsal horn neurons (Green and Dickenson, 1997). Given evidence that formalin evoked nociceptive behavior depends, at least in part, on capsaicin sensitive afferents (Peterson et al, 1997), and that afferent activity evoked during phase I of the formalin test (McCall et al, 1996) is comparable to that evoked by capsaicin (Schmelz et al, 2000), differences in GABA A receptor dependent signaling in these acute models is unlikely to depend on the initial afferent activity or which fibers are activated.…”
Section: Role Of Gabaa Receptors In Allodynia and Hyperalgesiamentioning
confidence: 99%
“…Several studies have implicated GABA B receptors in pain‐processing mechanisms in the spinal cord (Castro‐Lopes et al, 1995; Dirig and Yaksh, 1995; Lin et al, 1996; Green and Dickenson, 1997) and brainstem (Thomas et al, 1995, 1996; Hammond et al, 1998; Pinto et al, 2003). In the thalamic VB, a decrease in GABA B 1b receptor mRNA was recently observed on the side contralateral to the arthritic joint of MA rats (Ferreira‐Gomes et al, 2004).…”
mentioning
confidence: 99%